Health Capacity to Work at Older Ages in South Korea: Estimates and Implications for Public Pension Policies - Dohyung Kim (KDI Journal of Economic Policy, 2019)
Health capacity to work for the elderly is an essential piece of information for designing social policies in an aging society. Here, we assess the health capacity to work of older men in South Korea and provide a cross-country comparison. Following the methodology proposed by Milligan and Wise (2012), which uses the cohort mortality rate as a proxy for overall health status, we quantify the additional employment capacity of current older men in reference to the mortalityemployment relationship of a generation ago. Despite the high employment rate of older men in South Korea, we find substantial additional employment capacity among older men (those aged 55 or more) as of 2016 comparable in size to those found in other advanced countries. We also find evidence that older men are not merely capable of working but are also willing to work, and many of them are increasingly combining pension income and work. These findings suggest that labor supply disincentives for older men embedded in public pension systems in South Korea need to be thoroughly reexamined and adjusted accordingly lest they should inhibit the labor supply of older workers.
Keywords: J14; J21; J26; 330; Employment; Mortality; Work Capacity; Retirement; Public Pension